The nursing care after the eye enucleation - Galbarczyk, Katarzyna; Jędryczek, Beata; Galbarczyk, Andrzej (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Enucleation is an operation including removal of an eyeball or its remains. Extraocular muscles and conjunctiva are retained and artificial eyeball is implanted so that a patient can use mobile prosthesis, which looks like a natural eye. The aim of this paper is to discuss issues connected with nursing after the enucleation. The postoperative care should include applying dressings, appropriate medications, maintaining hygiene in the eyesocket as well as monitoring discharge from the eye and the implant adaptation in order to prevent any complications. In the case of the patient for whom the operation may mean loss of the sight the nursing must include adequate treatment. For a nurse equally important task is to teach a patient how to properly take care of the socket and the prosthesis. Enucleation is an irreversible operation, which is often a traumatic experience for the patients and his or her family, that is why an essential element of the treatment is psychological support and providing help that enables the patient to regain their physical fitness and self-reliance.